Marketing Strategy Analysis Generating of Traffic and Sales Conversion in Shopee (Case Studies at Roemah Aisya Store) - Novitasari; Hastuti Redyanita (Future Science)
Due to Covid-19 Pandemic, People finally make a business and fulfill their needs from home, one of them is to utilize the marketplace. Shopee as the highest marketplace has step-up its number of sellers, viewers, and transactions. More sellers in Shopee make the high seller competition climate. One of the sellers in Shopee, Roemah Aisya store, is going through this competition. There are more “braver” sellers that influence the turnover of Roemah Aisya. It declines in the year-end sales. The reasons for the declining turnover of Roemah Aisya are low traffic and sales conversion as well as it hasn’t applied accurate marketing strategies in the middle of pandemic and tight competition in Shopee. This research aims to give sale strategic solutions for the problems faced by Roemah Aisyah. This research uses a qualitative descriptive method by analyzing Roemah Aisya sales and strategic marketing that can produce traffic and sale conversion. The result of research explains that the unstable of Roemah Aisya sales is caused by low traffic and sale conversation. Roemah Aisya hasn’t optimized features and services in Shopee yet. These implications of research for the management field can give the marketing strategic plan and policy choice. It’s expected that the research result can give the information contribution especially for Roemah Aisya and MSMEs in general, that is marketing strategy generating traffic and sales contribution in Shopee. Besides that this research result can contribute some suggestions for digital business policymakers.